Devletin temel amaç ve ödevleri ışığında öznel gelişme hakkı (1982 anayasası M. 5) - Aslan, Betül (My University, 2007)
In first chapter of thesis right to development’s concept had been explained. Rights to development’s defination, dimension, history, quality and subject had been investigated. In second chapter of thesis lightings state’s fundamental aim and obligations right to subjective development had been researched in axsis 1982 Constitution. It had been explained The Constitution’s Made 17, Made 5, Made 65 and related to Constitution Court’s decision here.In the last chapter there had been evaluation and solution suggestion.
Keywords: Gelişme Hakkı_Hukuk